Optimalisasi Terapi Antidiabetik Oral pada Diabetes Mellitus Tipe 2: Studi Komparatif Monoterapi dan Kombinasi terhadap Outcome Glikemik Optimalisasi Terapi Antidiabetik Oral pada Diabetes Mellitus Tipe 2: Studi Komparatif Monoterapi dan Kombinasi terhadap Outcome Glikemik - Kiki Rawitri; Sri Wahyuni; Syilvi Rinda Sari; Ziza Putri Aisyia Fauzi; Ferina Septiani Damanik; Cut Intan Annisa Puteri; Anggitha Ningtias (JURNAL FARMASI DAN MAKANAN, 2026)
Type 2 diabetes mellitus (T2DM) is a chronic disease with a high prevalence in primary healthcare settings; however, real-world evidence regarding the effectiveness of oral antidiabetic therapies remains limited. This study aimed to compare the effectiveness of oral antidiabetic monotherapy and combination therapy in patients with T2DM at the Teladan Community Health Center (Puskesmas) in Medan. A non-experimental observational study with a cross-sectional design was conducted on 78 patients selected via systematic random sampling, utilizing medical records and data from the "referral-back" program covering the period from September to November 2025. Effectiveness was assessed using random blood glucose (RBG) levels and analyzed with the Kruskal–Wallis test. The results indicated that the combination of glimepiride and metformin was the most frequently used regimen (64.10%), followed by metformin monotherapy (26.92%) and glimepiride monotherapy (8.97%). The lowest mean RBG level was observed in the metformin monotherapy group (147.80±47.27 mg/dl), followed by the metformin-glimepiride combination group (168.72 ± 60.56 mg/dl) and the glimepiride monotherapy group (178±61.31 mg/dL); however, no statistically significant difference was found among the treatment groups (p=0.322). The study concludes that there is no significant difference in effectiveness between monotherapy and combination therapy regarding glycemic control, although metformin showed a trend toward better outcomes. These findings underscore the importance of an individualized approach to therapy for T2DM patients in primary healthcare facilities.